Assessment of Income and Employment Patterns in the Production and Marketing of Azalea (Rhododendron indica) in Kalimpong District of West Bengal, India - , Anmol Giri; , Dawjam Bhutia; , Md. Hasrat Ali (Archives of Current Research International, 2025)
Azalea (Rhododendron indica) is emerging as a profitable floricultural crop in the Kalimpong district of West Bengal, owing to its aesthetic appeal and adaptability to hill agro-climatic conditions. This study analyzes the income and employment dynamics of Azalea cultivation across Kalimpong-I and Kalimpong-II blocks, based on primary data collected from 50 sample growers through a stratified random sampling method during 2023–24. Economic indicators such as gross income (GI), returns over variable cost (RVC), family labour income (FLI), net income (NI), and returns to management (RM) were estimated by farm size. In Kalimpong-I Block, marginal farmers (<1 ha) reported the highest GI at ₹15.46 lakh and RM at ₹8.98 lakh, while semi-medium farmers (2–4 ha) had the highest returns per rupee (RPR) at 2.57. In Kalimpong-II Block, small farmers (1–2 ha) achieved the highest RM of ₹9.25 lakh, while semi-medium farmers had the highest RPR at 2.15. Employment analysis revealed that marginal farms in Kalimpong-II generated 101.22 man-days per season, compared to 73.12 man-days in Kalimpong-I. The study highlights that smaller farms exhibit higher profitability due to intensive use of family labour and efficient resource use. Findings suggest the need for targeted interventions such as improved access to credit, market linkages, and input subsidies to enhance the economic viability of Azalea farming in hill regions like Kalimpong.